Proposed Design of a Real-Time COVID-19 Pandemic Contact Tracing Using Mobile Phone - Ezenwa Nwawudu; Amanze Ikwu; Ugochi Ikwu; Nneoma Oparah; Stanley Nnorom (European Scientific Journal, ESJ, 2020)
As the virus that causes COVID-19 continues to spread from person to persons in communities and rampaging the world, the need for an effective real-time surveillance system becomes paramount. Advance contact tracing and detection of the persons with the virus represents one of the main strategies to prevent transmission. Although COVID-19 surveillance systems such as contact tracing mobile apps have improved the administration and management of virus, there are still challenges such as privacy, cost and ethical issues, the adoption of new technologies, standardized cases, and validly diagnosed case and validity. However, the current mobile apps contact tracing system adopted by different nations has complemented conventional tracing effort in fighting the virus. This proposal is a model for an interactive computer system using mobile phones and the internet for real-time collection and transmission of events related to COVID19. It will aid the administration and presumptive management of COVID-19 in the world, especially in rural areas. This proposal shows that a sophisticated COVID-19 surveillance system can be build using mobile phones with the right telecommunication technology partner.